The Use of Lactic Acid Bacteria Starter Cultures during the Processing of Fermented Cereal-Based Foods in West Africa: A Review - Amenan Anastasie Soro-Yao; Kouakou Brou; Georges Amani; Philippe Thonart; Koffi Marcelin Djè (Tropical Life Sciences Research, 2014)
Lactic acid bacteria (LAB) are the primary microorganisms used to ferment maize-, sorghum- or millet-based foods that are processed in West Africa. Fermentation contributes to desirable changes in taste, flavour, acidity, digestibility and texture in gruels (ogi, baca, dalaki), doughs (agidi, banku, komé) or steam-cooked granulated products (arraw, ciacry, dégué). Similar to other fermented cereal foods that are available in Africa, these products suffer from inconsistent quality. The use of LAB starter cultures during cereal dough fermentation is a subject of increasing interest in efforts to standardise this step and guaranty product uniformity. However, their use by small-scale processing units or small agro-food industrial enterprises is still limited. This review aims to illustrate and discuss major issues that influence the use of LAB starter cultures during the processing of fermented cereal foods in West Africa. Bakteria asid laktik (LAB) merupakan mikroorganisma primer yang digunakan untuk menapai makanan berasaskan jagung, sorgum atau sekoi yang diproses di Afrika Barat. Proses penapaian menyumbang kepada perubahan diingini dalam rasa, perisa, keasidan, pencernaan dan tekstur dalam bubur (ogi, baca, dalaki), doh (agidi, banku, komé) ataupun produk berbutir yang dikukus (arraw, ciacry, dégué). Sama dengan produk bijirin yang ditapai yang boleh didapati di Afrika, produk-produk ini terjejas dengan masalah kualiti yang tidak konsisten. Penggunaan kultur mula LAB semasa penapaian doh bijirin merupakan subjek yang semakin menarik perhatian dalam usaha memiawaikan proses ini dan menjamin keseragaman produk. Walau bagaimanapun, pengunaan oleh unit pemprosesan secara kecilan ataupun perusahaan agro-makanan masih terbatas. Ulasan ini bertujuan untuk menggambarkan dan membincangkan isu-isu utama yang memberi kesan terhadap penggunakan kultur mula LAB semasa proses penapaian makanan bijirin di Afrika Barat.